AB0220 Myeloid-Related Proteins 8 and 14 (MRP 8/14) – Potential Biomarkers of Disease Activity of Arthritis in Children with Trisomy 21?. (9th June 2015) - Foley, C.; Killeen, O.; MacDermott, E.J.; Veale, D.
Abstract : Background: JIA is an umbrella term used to describe a heterogeneous group of diseases. To date no specific markers exist in clinical practice to predict disease activity & outcome. Down's Arthropathy (DA) was first described in the literature in 1984. There is a paucity of data with regards to the features & pathogenesis of this arthritis. MRP 8/14 are calcium-binding proteins secreted by infiltrating phagocytes in synovial inflammation. Studies have shown that their serum (Se) concentrations correlate sensitively & specifically with synovial inflammation in JIA. There is limited literature on the use of synovial fluid (SF) samples of MRP8/14 as a biomarker in JIA. To date there have been no studies looking specifically at Se or SF levels of MRP 8/14 in DA Objectives: To evaluate the use of standard (ESR and CRP) & novel (MRP 8/14) inflammatory markers as biomarkers of disease activity in DA & JIA Methods: Over a 1-year period, new cases of JIA & DA attending the NCPR had blood drawn to measure their CRP, ESR & MRP 8/14 levels. Corresponding Active Joint Count (AJC) was documented. Paired SF samples were taken for analysis from children requiring steroid JIs as treatment for their arthritis. Se & SF concentrations of MRP 8/14 were determined by sandwich ELISA. CRP & ESR were measured as part of routine clinical assessment. Results: 49 children (27 JIA, 22 DA) had Se taken for CRP, ESR & MRP 8/14 levels. 20 (18 JIA, 2 DA) had paired SF samples taken. The average AJC was 4 (1-11). 18 Se samples were taken from healthy children with T21 as a second comparison group to the DA cohort. In DA, a significant positive correlation was detected between AJC & both ESR & MRP 8/14 (SF). A similar pattern was seen in the JIA cohort, in addition SeMRP 8/14 levels positively correlated with their paired SF level. CRP did not correlate with AJC, ESR or MRP 8/14 (SF) in either group. No significant correlation was noted between Se & SF MRP 8/14 levels in DA. In fact, no significant difference between SeMRP 8/14 levels in the DA & T21 was noted. Conclusions: MRI with contrast remains the gold standard for diagnosis of synovitis. In reality, clinical assessment is the major diagnostic tool. DA is a more challenging condition than JIA in light of confounding illness & the often-associated developmental delay & non-verbal state. In DA a simple biomarker of disease would be invaluable. We have shown that CRP is a poor marker of disease activity in JIA & DA so the need for a more specific biomarker is evident. Our preliminary results suggest that children with DA (& JIA) have elevated SF levels of MRP 8/14 that correlate to disease activity. In JIA, SF concentrations of MRP 8/14 are significantly higher than their paired Se samples, however our results show significant positive correlation between the two. This suggests that SeMRP 8/14 levels are potentially accurate markers of SF levels, & in turn accurate markers of disease activity in JIA. This was not the case in our DA cohort. In fact, we found that there was no significant difference in SeMRP 8/14 levels between our DA & T21 cohort. Unlike in JIA, SeMRP 8/14 levels were not shown to be a useful biomarker of disease activity in DA. Does this suggest that DA has a different pathophysiology than JIA? Further research is required to verify our findings, & to expand our understanding of this inflammatory condition. Disclosure of Interest: None declared